2019
DOI: 10.1021/acsomega.8b03276
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Reaction Mechanism during Li Uptake and Release of Nanosized “NiFeMnO4”: Operando X-ray Absorption, X-ray Diffraction, and Pair Distribution Function Investigations

Abstract: Here, we report that the trimetallic nanosized oxide NiFeMnO 4 consists of a mixture of NiO and a strained cubic spinel phase, which is clearly demonstrated by analysis of the pair distribution function (PDF) and synchrotron X-ray data. Such a finding can easily be overlooked by using only inhouse X-ray powder diffraction, leading to inaccurate assumption of the stoichiometry and oxidation states. Such advanced characterization is essential because a homogeneous distribution of the eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…The results of CoFe 2 O 4 and NiFeMnO 4 shown that with the lithium consumption, the initial spinel phase transformed into NaCl-like structure, which accounted for the cation arrangement with value state changing. The capacity degradation was found in both materials owing to formation of inactive metal particles (Co, Ni) [141,142]. A similar migration of site occupation was found in ZnFe 2 O 4 with the lithiation process, leading to three critical reduction products Li x ZnFe 2 O 4 (x = 0.5, 1, 2) (Fig.…”
Section: In-situ Xassupporting
confidence: 64%
See 1 more Smart Citation
“…The results of CoFe 2 O 4 and NiFeMnO 4 shown that with the lithium consumption, the initial spinel phase transformed into NaCl-like structure, which accounted for the cation arrangement with value state changing. The capacity degradation was found in both materials owing to formation of inactive metal particles (Co, Ni) [141,142]. A similar migration of site occupation was found in ZnFe 2 O 4 with the lithiation process, leading to three critical reduction products Li x ZnFe 2 O 4 (x = 0.5, 1, 2) (Fig.…”
Section: In-situ Xassupporting
confidence: 64%
“…A number of works were carried out on the conversion reactions of spinel materials, including ZnFe 2 O 4 , CoFe 2 O 4 , NiFeMnO 4 [140][141][142]. Through in-situ XAS combined with other operando techniques, the evolutions of crystalline structure and valent state were studied during the lithiation in detail.…”
Section: In-situ Xasmentioning
confidence: 99%
“…Simultaneously, the pre-edge signal slightly shifts toward 5988.7 eV gaining intensity and reaching maximum intensity at the discharged state, resembling that of nanocrystalline elemental Cr. The differences between the spectrum of the discharged sample and the Cr foil is a phenomenon known for metal nanoparticles and amorphous alloys , caused by strong disorder and large amounts of surface atoms/defects altering scattering paths, compared to well-crystalline phases. At this point of data analysis, the formation of CrP instead of elemental Cr cannot be ruled out, because the present spectrum shows similarities with that of literature data for crystalline CrP .…”
Section: Resultsmentioning
confidence: 99%
“…[109,110] PDF and difference PDF were also used to examine other solid state reactions. [111][112][113] While these experiments show the promise of using total scattering investigations to follow solid state reactions, there remain significant experimental challenges. The most significant are the subtraction of background scattering and the lack of a method to analyze total scattering from samples that are textured.…”
Section: Pair Distribution Function Analysismentioning
confidence: 99%